Pengaruh E-Service Quality dan E-Trust terhadap E-Loyalty Melalui E-Satisfaction Sebagai Variabel Intervening: Studi pada Pengguna BSI Mobile PT. BSI di Kota Malang - Aisyah Nur Rahmadina; Irmayanti Hasan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to determine the effect of e-service quality and e-trust on e-loyalty through e-satisfaction as an intervening variable for BSI customers in Malang City who use BSI Mobile. This research uses a quantitative approach with explanatory research methods. The location of this research is in Malang City. The sample used was 175 respondents. Data collection techniques are questionnaires and literature studies. Data analysis techniques using smartPLS software with Partial Least Square (PLS) techniques. From the results of this study shows that e-service quality has no effect on e-loyalty. E-trust has no effect on e-loyalty. E-satisfaction affects e-loyalty. E-service quality affects e-loyalty through e-satisfaction as an intervening variable and e-trust affects e-loyalty through e-satisfaction as an intervening variable.